SOME CONSIDERATIONS ON TEACHING ENGLISH TO CHILDREN IN PRE-SCHOOL EDUCATIONAL INSTITUTIONS (Scientific journal of the Fergana State University, 2024)
This article provides some comments on the reforms implemented in our country and the further improvement and development of the pre-school education system, and the use of psychological and pedagogical methods via educational activities in pre-school organizations.